Sertralina no tratamento de pacientes com depressão maior leve e moderada: Estudo multicêntrico brasileiro - Neto, Abrahão Afiune; Barea, Liselotte Menke; Calamita, Zamir [UNESP]; Cavalcanti, Fernando; Pippa, Maria Guadalupe Barbosa (My University, 2007)
Introduction: To evaluate the efficacy, safety, and tolerability of sertraline for the treatment of Brazilian patients with mild to moderate major depression. Patients and methods: Patients were 18 years old or older treated on an out-patient basis. Previous medications were stopped for a 2-week washout period. Afterwards, patients received sertraline, initial dose of 50 mg/day up to the 4 th week. The dose could then be increased up to 200 mg/day according to the efficacy and tolerability. Therapeutic efficacy was evaluated with the Montgomery-Asberg Depression Rating Scale (MADRS), Hamilton scale for depression (HAM-D), and Clinical Global Impression (CGI). Results: 51 patients (42 women) were evaluated regarding efficacy and safety. Treatment with sertraline significantly decreased scores of MADRS, HAM-D e ICGfrom 15.7 ± 6.1; 12.2 ± 3.9 e 3.5 ± 0.6 to 6.2 ± 6.5; 5.4 ± 4.7 e 2.3 ± 1.0 (P < 0.0001), respectively. Sertraline was well tolerated. Gastro-intestinal upset (N=14; 24.6%), headache (N=7; 12.3%), sleep alterations (H-7; 12.3%), dizziness (N-4; 7.0%), and anorexia (N=4; 7.0%) were the most common adverse events. Six patients discontinued the treatment due to adverse events. Conclusion: Sertraline is efficient and presents a favorable safety and tolerability profile for the treatment of Brazilian patients with mild to moderate major depression. © Copyright Moreira Jr. Editora.
Sertraline for the treatment of mild to moderate major depression: Brazilian multicenter study
Keywords: Depressive disorder; Drug therapy; Serotonin uptake inhibitors; Sertraline; sertraline; adult; anorexia; Clinical Global Impression scale; controlled study; depression; disease severity; dizziness; drug efficacy; drug safety; drug tolerability; drug withdrawal; female; gastrointestinal symptom; headache; human; major clinical study; male; sleep disorder